Determining the need for early orthodontic treatment of children with harmful habits - E. A. Ogonyan; Yu. A. Makedonova; V. R. Ogonyan; L. A. Devyatchenko; M. V. Kabytova; V. R. Gladun (Эндодонтия Today, 2024)
AIM. To determine the need for early orthodontic treatment of children with bad habits, to assess the need for complex treatment and involvement of doctors of diﬀerent proﬁles to eliminate the pathology of the maxillofacial region.MATERIALS AND METHODS. A comprehensive examination of children with bad habits at the age of 1 to 3 years was carried out, which included: questioning of parents, study of dental status, distribution of children into groups depending on the degree of need for orthodontic treatment.RESULTS. The ﬁrst group included 14 children (22.58 % ± 1.26) who had bad habits but did not need specialized orthodontic treatment. The second group included 23 patients (37.09 % ± 1.01) who required orthodontic treatment by myogymnastics. Patients of the third group, which included 8 patients (12.9 % ± 1.4), required specialized orthodontic treatment with prescription of removable appliances of mechanical and (or) functional action. The fourth group consisted of 10 children (16.12 % ± 1.35) who required complex dental treatment. The ﬁfth group of need for orthodontic treatment included 7 children (11.29 % ± 1.43) who required not only dental treatment but also the involvement of general medical specialists.CONCLUSION. Among young children the prevalence of bad habits remains high and the variety of their clinical manifestations does not always provide only orthodontic treatment.